2020
DOI: 10.1155/2020/5454197
|View full text |Cite
|
Sign up to set email alerts
|

Acute Symptomatic Calcific Discitis Mimicking a Septic Spondylodiscitis

Abstract: Acute symptomatic calcific discitis is a poorly understood condition that has been mostly reported in children. Cases in adults have been scarcely reported and may mimic an infectious process. Imaging, including computed tomography, can show the disc calcification but might fail to show it because its resorption can occur early after the onset of symptoms. We report the case of an adult patient presenting with severe cervical-dorsal junction pain, fever, high C-reactive protein (CRP) levels, and imaging findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…However, an infective process may additionally demonstrate diffuse oedema and contrast enhancement of vertebral bodies. It is suggested that calcification of the nucleus pulposus on CT is crucial to the diagnosis of calcific discitis; 1,2 however, in this case, it allayed suspicion of an infective process. This case suggests extrusion of calcific material may coincide with an infective discitis.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…However, an infective process may additionally demonstrate diffuse oedema and contrast enhancement of vertebral bodies. It is suggested that calcification of the nucleus pulposus on CT is crucial to the diagnosis of calcific discitis; 1,2 however, in this case, it allayed suspicion of an infective process. This case suggests extrusion of calcific material may coincide with an infective discitis.…”
Section: Discussionmentioning
confidence: 92%
“…Disc calcifications are usually asymptomatic; however, if they extrude into surrounding tissues, they induce acute pain and inflammation. Symptomatic calcific discitis is clinically indistinguishable from infective discitis, with both conditions manifesting fever and elevated inflammatory markers 1,2 . In patients with symptomatic calcific discitis, they often spontaneously improve within a week.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations